Cacoheterotanais rogerbamberi, a new genus and species of leptocheliid Tanaidacea (Crustacea: Peracarida) from shelf-waters of the Gulf of Mexico - Morales-Núñez, Andrés G.; Heard, Richard W. (Zootaxa, 2015)
A new leptocheliid tanaidacean, Cacoheterotanais rogerbamberi gen. et sp. n., is described from the Continental Shelf of the eastern Gulf of Mexico at depths ranging from 10 to 30 m. The new monotypic genus and species is distinguished from the other genera within the Pseudonototanais complex, or genus-group, (Cocotanais, Heterotanais, Makassaritanais, Ogleus, and Pseudonototanais) by a combination of characters, including the (1) male antennule with three peduncular and three flagella articles, (2) male and female both having three articles in the uropodal endopod, (3) basis of the female maxilliped with three pairs of long distal setae, and (4) differences in the morphology, setation and shape of the male cheliped. A key and table are presented to further distinguish C. rogerbamberi from the genera and species within the Pseudonototanais complex.